2020
DOI: 10.1111/evj.13349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of working equid welfare across three regions of Mexico

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Poor body condition and wounds were the most common welfare problems observed across all study locations and this suggests that the interventions put in place have been effectively targeting these most prevalent issues. Previous research in the study area has demonstrated that role, location and species have an effect on equid welfare [ 42 ] although the natural covariance of these factors means that it is not possible to isolate their relative effects. In order to ensure that the influence of location and role were not confounding the effect of intervention level on welfare, a separate analysis of riding equids in the state of Veracruz only was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Poor body condition and wounds were the most common welfare problems observed across all study locations and this suggests that the interventions put in place have been effectively targeting these most prevalent issues. Previous research in the study area has demonstrated that role, location and species have an effect on equid welfare [ 42 ] although the natural covariance of these factors means that it is not possible to isolate their relative effects. In order to ensure that the influence of location and role were not confounding the effect of intervention level on welfare, a separate analysis of riding equids in the state of Veracruz only was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…As women did not generally use their equids, they did not view themselves as ‘owners’ of equids and therefore often weren’t able to access the social and educational benefits of ownership or have involvement in decision making regarding their equids.The demographic of working equid ‘owners’ has been reflected in studies globally [ 30 , 42 , 43 ], with recognised differences between predominantly female ‘caregivers’ and male ‘owners’ [ 4 , 44 ]. This theme is mirrored in agriculture, where women are often described as ‘caregivers’ to food-producing livestock [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to ensure appropriate management and routine care to maintain good health among donkeys. Different types of nutrition, stabling facilities, activity, environment, health care, and culture can influence the welfare, development of disease and average breeding life of horses and donkeys (7,(13)(14)(15). However, donkeys often suffer significant health problems owing to physiologic characteristics and stoical behavior which are often misinterpreted by owners (16).…”
Section: Introductionmentioning
confidence: 99%
“…Donkeys often do not exhibit obvious clinical signs despite suffering from severe or even life-threatening conditions (17). The characteristics in behavior, physiology and health have been recognized by some donkey researchers, para-Governmental bodies and owners, who have developed management guidelines for disease prevention (18,19) and applied improved management practices to control disease risks (15,17).…”
Section: Introductionmentioning
confidence: 99%